Replacement of Antarctic krill (Euphausia superba) by extruded feeds with different proximate compositions: effects on growth, nutritional condition and digestive capacity of juvenile European lobsters (Homarus gammarus, L.). (12th May 2021) - Goncalves, Renata; Gesto, Manuel; Teodósio, Maria Alexandra; Baptista, Vânia; Navarro-Guillén, Carmen; Lund, Ivar
Abstract: Extruded feeds are widely used for major aquatic animal production, particularly for finfish. However, the transition from fresh/frozen to extruded/pelleted feeds remains a major obstacle to progressing sustainable farming of European lobster ( Homarus gammarus ). The aim of the present study was to investigate the effects of using extruded feeds with different protein levels and lipid/carbohydrate ratios on growth, feed utilisation, nucleic acid derived indices (sRD) and digestive enzymatic activity of H. gammarus juveniles. Six extruded feeds were formulated to contain two protein levels (400 and 500 g/kg), with three lipid/carbohydrate ratios (LOW – 1:3; MEDium – 1:2; HIGH – 1:1). The extruded feeds were tested against Antarctic krill ( Euphausia superba ) used as control (CTRL). Overall, the CTRL and 500MED feed supported the highest growth and nutritional condition estimated by means of sRD, while the poorest results were observed for the 400HIGH and 400MED groups. The FCR was significantly lower in the CTRL than all extruded feeds, among which the most efficient, i.e., lower FCR, was the 500MED. The highest activity of trypsin and amylase in lobsters fed the 400MED and 400HIGH feeds points to the activation of a mechanism to maximise nutrients assimilation. The highest lipase activity observed for the 500LOW and 500MED groups indicates a higher capacity to metabolise and store lipids. Overall, the results suggest that the 500MED feed (500 g/kg protein, 237 g/kg carbohydrates and 119 g/kg lipids) is a suitable extruded feed candidate to replace Antarctic krill, commonly used to grow lobster juveniles.